“EFECTO DEL CRECIMIENTO ECONÓMICO SOBRE LA CALIDAD AMBIENTAL: CURVA DE KUZNETS PARA PAÍSES DE LATINOAMÉRICA” - Armijos Maza, Kevin Bryan (2021)
The main problem on which the research is based for its development is the environmental deterioration produced by the amount of methane emissions caused by the different environmental pollutants. The objective of this work is to estimate the effect of economic growth on environmental quality, which is measured by methane emissions, and using electrical energy consumption and land use as control variables, through the environmental Kuznets curve. for Latin American countries. The methodology uses a model with panel data and cointegration techniques, based on data from the World Development Indicators and the Food and Agriculture Organization of the United Nations. The main result indicates that economic growth has a positive relationship with methane emissions, with cointegration in the long term. At the same time, a bidirectional Granger causality between economic growth and methane emissions is evident. Finally, it is concluded that economic growth causes an increase in methane emissions, therefore, the CKA for Latin America is not fulfilled, therefore, Latin America is still in the first phase of the CKA, since it has not reached the point where methane emissions are reduced as economic growth increases. The main recommendation is that Latin American countries focus on the regulation and reduction of methane emissions, through the implementation of public policies to promote the green economy.